Upaya Penurunan Angka Kematian Ibu Melalui Edukasi Kesehatan Reproduksi dan Persiapan Kehamilan Yang Sehat - Noor Rochmah Ida Ayu Trisno Putri; Tin Utami -; Etika Dewi Cahyaningrum; Suci Khasanah -; Adiratna Sekar Siwi (Borneo Community Health Service Journal, 2023)
One of the health indicators in a country can be seen from the prevalence of maternal mortality (MMR). The maternal mortality rate in Indonesia has experienced a drastic increase. In 2019 the maternal mortality rate reached 4,221 people and increased in 2021 to reach 7/389 people. This condition is not in line with the global maternal mortality rate target of less than 70 per 100,000 live births in 2023. So an effort is needed to reduce MMR, prevent the risk of emergency pregnancy and provide reproductive education. The purpose of community service activities is to increase mother's knowledge to maintain women's health so that it can reduce maternal mortality. The target of the activity is mothers or women of childbearing age totaling 17 people. The activity was carried out at the Permata Harmoni Residential PKK Association, Ledug, Banyumas, Central Java. The activity will be carried out in March 2023. The activity method is carried out with the stages of preparation, implementation, evaluation and making a follow-up plan. The results of community service activities found an increase in mother's knowledge regarding reproductive health, from 47.0% before being given education to 70.6% after getting education. This activity was concluded to be able to increase mother's knowledge so that it is recommended for health service providers to routinely carry out health promotion, especially in terms of maternal reproductive health so as to prevent higher maternal mortality rates